Optimal exercise parameters of Baduanjin for balance in older adults: a systematic review and meta-analysis - Yang, Yikun; Li, Enjing; Gong, Zixin; Tualaulelei, Mauri; Zhao, Zhiwei; Zhang, Zhiyan (Frontiers in Public Health, 2025)
PurposeBaduanjin represents an affordable and secure method of exercising both the mind and body, and has been observed to enhance balance in older adults. Nevertheless, the existing research on the impact of Baduanjin on various balance functions is still insufficient, and the optimal dosage parameters for performing Baduanjin exercises have not been studied.MethodsTo conduct a systematic review and meta-analysis, five English databases and three Chinese databases were performed. Relevant studies were searched by GOOGLE SCHOLAR, Web of Science, Cochrane, Embase, Pubmed, CNKI, SinoMed, and WangfangMed using “Baduanjin” and “balance.” Subgroup analyses were conducted to investigate the influence of different exercise parameters on the observed outcomes. Meta-regression was employed to identify potential moderating factors. The Physical Therapy Evidence Database (PEDro) scale was used for quality assessment.ResultsA total of 40 studies were included in the analysis, while the majority of studies report promising outcomes, the overall quality of these studies is relatively low. The results of the meta-analysis showed Baduanjin significantly enhanced static balance (SMD = 0.87, 95%CI: 0.69–1.05), dynamic balance (SMD = 0.85, 95%CI: 0.50–1.19), proactive balance (SMD = −1.00, 95%CI: −1.33–−0.67) and balance test battery (SMD = 1.04, 95%CI: 0.81–1.28) in older adults. Additionally, the findings indicated a notable reduction in the risk of falls (SMD = −2.19, 95%CI: −3.35–−1.04) and an improvement in fall efficacy (SMD: 0.57, 95%CI: 0.36–0.78).ConclusionBaduanjin has been demonstrated to improve balance and reduce the risk of falls in older adults. Studies have found that significant gains begin to be achieved with a minimum of 12 weeks of practice and that 30–49 min of practice, 5–7 times per week, works best for developing different balances. However, most of the included studies were limited by a lack of blinding and follow-up visits, and there was an insufficient number of short-term or long-term studies to establish complete optimal parameters robustly.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=548345, identifier: CRD42024548345.